Involvement in sports clubs and informal sport activities of primary and secondary school children in Liechtenstein - Jürgen Kühnis; Beat Wachter; Christian Frommelt (University of Maribor Press, 2016)
Sport involvement among children and adolescents has been a central field of research in sport science since years. This paper documents the participation of 11- to 15-year-olds in sport clubs and informal sport activities in Liechtenstein and examines possible gender- and age-specific differences. The analysis is based on four cross-sectional studies from 2004 to 2015 and includes the data of 1'262 children in primary (5th grade) and secondary (7th and 9th grades) school. According to our findings sports and exercise are considered to be one of the main leisure-time activities for all school levels (irrespective of gender). The percentage of fully sport-abstinent adolescents by 11- and 13-year-olds is about 5 %; by 15-year-olds is around 10 %. The culmination of sports club membership (with current 84.7 %) appears to be at the age of 11 (5th grade). After the switch to secondary school the sports club commitment tends to decrease, while the high attendance of the informal sport activities (>85 %) shows relatively stable age development. In contrast to other child and youth studies, our data indicates a levelling tendency and dissolution of classic gender differences not only in sports club commitment but also in informal sports among girls and boys.